KUALITAS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALU - Rahmawaty, Rahmawaty (Katalogis, 2016)
The purpose of this study was to determine the service quality Electronic Identity Card at the Office of Population and Civil Registration Palu. This research is classified as descriptive research. With a qualitative approach. This research was held at the Office of Population and Civil Registration Palu. The theory is used to measure the quality of service is a theory proposed by Tjiptono (1995: 14), dimensional quality of service includes Courtesy and hospitality, Responsibility, Convenience, Comfort, and Completeness Facility. This type of data consists of primary data and secondary data. Retrieval and Data Collection is done through observation, interview and documentation. Data analysis was carried out by means of data collection, data presentation and inference. These results indicate that the quality of service indicators Courtesy and hospitality in Service and Ease indicators already showed a good condition. While indicators of responsibility, comfort, and indicators Complete facilities need to be improved or that are in unsatisfactory condition.